2003
DOI: 10.48044/jauf.2003.009
|View full text |Cite
|
Sign up to set email alerts
|

Application and Comparison of Three Tomographic Techniques for Detection of Decay in Trees

Abstract: This paper reports application of electric, ultrasonic, and georadar tomography for detection of decay in trees and their comparison with the traditional penetrometer. Their feasibility in arboriculture is also evaluated, critically considering some "open problems." The experiments were carried out in an urban environment on two plane (Platanus hybrida Brot.) trees. Both trees, after felling, showed extensive white rot in the central cylinder. The electric tomography revealed low resistivity zones roughly cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 22 publications
2
24
0
3
Order By: Relevance
“…The adoption of advanced technological methods of measuring decay or determining strength promises to improve the understanding the likelihood of failure due to decay. The effectiveness of technologically advanced decay-detecting devices is still unclear (Nicolotti et al 2003;Gilbert and Smiley 2004;Deflorio et al 2008;Wang and Allison 2008;Butnor et al 2009;Seifert et al 2010). Improving the accuracy of such devices, as well as the images they produce, would facilitate the numerical evaluation of decayed cross sections.…”
Section: Decay and Strength Lossmentioning
confidence: 99%
“…The adoption of advanced technological methods of measuring decay or determining strength promises to improve the understanding the likelihood of failure due to decay. The effectiveness of technologically advanced decay-detecting devices is still unclear (Nicolotti et al 2003;Gilbert and Smiley 2004;Deflorio et al 2008;Wang and Allison 2008;Butnor et al 2009;Seifert et al 2010). Improving the accuracy of such devices, as well as the images they produce, would facilitate the numerical evaluation of decayed cross sections.…”
Section: Decay and Strength Lossmentioning
confidence: 99%
“…The presence of wider annual rings was noticed in some sections, corresponding either to more favorable climatic conditions in the development of the tree (Rinn 1988;Beldeanu 1999;Beldeanu 2008), or to the local conditions of tree growth. These wider annual rings suppose a different proportion of early and latewood (Filipovici 1964;Beldeanu 1999;Beldeanu 2008), which influences the wood density in the area (Nicolotti et al 2003;Lin et al 2008;Liang and Fu 2012;Feng et al 2014;Li et al 2014) and, finally, the speed of sound propagation (Sandoz and Lorin 1996;Wang et al 2007;Leboucher 2014). The comparative analysis of the tomograms with the visual appearance after cutting a slice with a chain-saw showed that some small defects located inside the stem were not evident in the tomogram (Figs.…”
Section: Comparison Of Tomograms With the Real State Of The Wood At T...mentioning
confidence: 99%
“…Hasil asesmen kesehatan pohon secara visual dapat didukung dengan pengujian kondisi pelapukan batang utama menggunakan teknologi tomografi (Rachmadiyanto et al 2017). Penelitian menggunakan teknologi tomografi telah dilakukan oleh Nicolotti et al (2003), Karlinasari (2015), dan Göcke (2017) yang menunjukkan hasil bahwa penggunaan teknologi tomografi efektif untuk mendeteksi kelapukan batang utama pohon. Dengan demikian, penggabungan asesmen dari pengamatan visual dan pengujian dengan alat teknologi tomografi diharapkan mampu meningkatkan ketepatan hasil pengamatan kondisi kesehatan pohon.…”
Section: Pendahuluanunclassified